Relapsing De Novo Membranous Nephropathy - Ala Ali; Huda Al-Taee; Thaer J. Kadhim (Case Reports in Transplantation)
Allograft membranous glomerulopathy can be a recurrent or de novo disease. Both instead have different underlying immune pathophysiology and disease pattern. While the introduction of ANTI-PLAR2 and THS7A brought new insights into the management of Immune/primary MN, the treatment of de novo MN is not clear. Relapsing de novo MN in a kidney transplant was rarely reported. Here, we present a case of relapsing de novo MN without evidence of rejection and a gratifying response to rituximab.